FACTOR ASSOCIATED WITH GASTRITIS INCIDENCE IN PEOPLE PULAU TENGAH VILLAGE , KERINCI REGENCY - Oktariyani Dasril; Firda Rosalina; Wiya Elsa Fitri (Jurnal Kesehatan Medika Saintika, 2022)
This research was motivated by the high incidence of gastritis at the Jujun Inpatient Health Center in 2020was 924 cases. Gastritis can strike anyone.. The aims of this study was to determine the factors associated with the incidence of gastritis in people in Pulau Tengah Vilaage, Kabupaten Kerinci. This type of analytic research with cross-sectional design. The population of all people aged 20-44 years in Pulau Tengah Vilage is 90 people. Sampling using a to saturated sampling technique. Data collection was conducted manually from July-September 2021. The data were analyzed univariate and bivariate using the Chi-Square test with a significance level of 95% = 0,05. The result showed that as many as 54,4% respondents had gastritis. More than half of respondents are 52,2% have a poor eating habits, 56,7% respondents often consumed NSAID, and 56,6% respondents had poor coffee habits. The results showed that there was a relationship between eating habits and the incidence of gastritis with a p value = 0,003. There is a relationship between NSAID consumption and the incidence of gastritis with a p value = 0,000. There is a relationship between coffee consumption and the incidence of gastritis with a p value = 0,000. Factors of eating habits, consumption of NSAIDs, and coffe consumption are associated with the incidence of gastritis. As a result most people in Pulau Tengah vilaage faced gastritis. It is hoped that the community in Pulau Tengah Village should be able to maintain good consumption patterns to prevent gastritis